(untitled) (World Economics and Finance Bulletin, 2022)
This article discusses the possibilities of chemical finishing of mixed polyesterbamboo fabric with dispersed dyes. The purpose of this study is to obtain a mixed fabric based on bamboo and polyester fiber and to develop a technology for dyeing with disperse dyes. The object of the study was a blended fabric made of polyester and bamboo fibers with technical characteristics, 140 cm wide, 36 g/m2 surface density, the number of threads per 10 cm of fabric, 352 warp, 350 weft